(untitled) (Comparative Professional Pedagogy, 2021)
The article highlights the need to study the problem of forming the entrepreneurial competence of the future primary school teacher in domestic and foreign experience. It is noted that the development of entrepreneurship of European citizens and organizations has been one of the key policy objectives of the European Union and the Member States for many years; the understanding that entrepreneurial skills, knowledge and guidelines can be learned is deepening, which leads to the widespread development of entrepreneurial thinking and entrepreneurial culture, useful both for individual citizens and for society in particular. The structure of entrepreneurial competence Entre Comp is presented in this article. This structure presents a conceptual model and definition of entrepreneurial competences, offers ways and means to improve the entrepreneurial capacity of citizens and organizations in Europe. The experience of entrepreneurial training as a part of the educational process in the United Kingdom is examined here. It is aimed at the purposeful formation of the qualities of the entrepreneur’s personality and competence in the organization and implementation of small business projects. It is stated that there is no established interpretation of the concept of "entrepreneurial competence" in scientific and pedagogical works. Emphasis is placed on the study of entrepreneurial competence as an integrative quality of personality, a complex of personal or business qualities, a model of behavior based on critical thinking skills, creativity, initiative, perseverance, ability to solve problems and cooperate, create and implement innovations. The need to teach entrepreneurship, the formation of a modern teacher of entrepreneurial competence at the national level (Professional Standard), in the Ukrainian-Polish project “Lessons with an entrepreneurial background”, research studios of Ukrainian and foreign scientists are declared in this article.